Synthesis and Photophysical Properties of 3-Amino-4-arylpyridin-2(1Н)-ones - Shatsauskas, Anton L.; Abramov, Anton A.; Chernenko, Sergey A.; Kostyuchenko, Anastasia S.; Fisyuk, Alexander S. (Synthesis, 2020)
A method has been developed for the preparation of oxazolo-[5,4-b]pyridin-2(1H)-ones based on the Hoffmann reaction of 2-oxo-1,2-dihydropyridine-3-carboxamides. Hydrolysis of oxazolo[5,4-b]pyridin-2(1H)-ones and the Hoffmann reaction of 2-oxo-1,2-dihydropyridine-3-carboxamides yielded 3-aminopyridin-2(1H)-ones, including 4-aryl substituted derivatives in the series, for which effective phosphors with a quantum yield of up to 0.78 were detected. Photophysical properties of 3-aminopyridin-2(1H)-ones were studied by UV and luminescence spectroscopy methods, and the relationship between their structure and photophysical properties was revealed.
Keywords: оxazolo[5,4-b]pyridin-2(1H)-one; Hofmann reaction; 3-aminopyridin-2(1H)-ones; luminophores; electronic spectra